Legal Review of Clauses in Fire Insurance Policies - Mas Rara Tri Retno Herryani (Jurnal Cakrawala Hukum, 2023)
Insurance is an important thing to have if there is a risk of something detrimental happening. Insurance is regulated in laws and regulations. In addition, setting fire insurance policies based on applicable legal norms will create legal certainty for the parties involved in the insurance agreement. Normative legal research which is often also called doctrinal legal research focuses on activities carried out by examining literature and secondary data in the form of primary and secondary legal materials. The insurance policy contains the terms contained in the insurance agreement. This policy can be considered the same as a clause in a civil agreement. A cause is said to be contrary to the law if the contents of the cause in the relevant agreement are contrary to the law if the contents of the cause in the relevant agreement are contrary to the applicable law. Determining whether the cause of an agreement is contrary to decency (geode seen) is not an easy matter because the term deficiency is very abstract, the contents of which can vary between one region and another or between one community group and another. In addition, people's evaluation of disability can also change according to the times.